PENGARUH MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TERHADAP HASIL BELAJAR PRAKARYA DI KELAS VIII SMPN 1 PADANG PANJANG - Hadi, Yan Hadi Ananda; Mulyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of instructional media plays an important role in supporting the integration of the learning process. Properly selected media are flexible and can be applied to various levels of students as well as different learning activities. This study aimed to determine the effect of instructional media on the learning outcomes of Craft subject students in class VIII at SMPN 1 Padangpanjang. Based on the theoretical framework, audiovisual learning media are considered capable of providing more concrete, structured, and repeatable learning experiences according to students’ needs, thereby potentially improving students’ understanding and practical skills. This research employed a quantitative approach with an experimental design. The sample consisted of students from classes VIII D and VIII F, selected using a simple random sampling technique. The findings revealed an improvement in learning outcomes in both groups. In the experimental class, the mean pre-test score of 49.29 increased to 88.00 in the post-test. Meanwhile, in the control class, the mean pre-test score of 55.41 increased to 68.30 in the post-test. These results indicate that the improvement in the experimental group was significantly higher than that of the control group.